The Trillion Dollar War : The U.S. Effort to Rebuild Afghanistan, 1999-2021 - Amiri, Abid, 1989- (Book collections on Project MUSE., 2021)
"The Trillion Dollar War is the culmination of an Afghan's personal life story weaved into academic understanding and coupled with professional experience in the field of development. It is written for Afghans, Afghan policymakers, and those in the West and broader international community who truly wish to see Afghanistan progress after more than 20 years of war. This title offers a perspective on how the United States and Afghanistan got where they are and proposes ways to find the economic growth that has until now remained elusive"--